Theoretical Investigation of Mono- and Di-Chloro-Substitient Effects on the Insulation and Greenhouse Properties of Octafluorocyclobutane - Cheng, Lin; Qin, Zhaoyu; Zhang, Chaohai; Shi, Huixuan; Zhao, Kun; Xie, Xiaoyu; Ma, Haibo (Frontiers in Chemistry, 2016)
Octafluorocyclobutane, c-C4F8, and its derivatives are regarded as promising replacements of insulation gaseous SF6, which are currently widely used in electric equipment but suffer greatly from its greenhouse effect. Based on the recent finding that the dielectric and thermodynamics properties of insulating gases are greatly dependent on the molecule’s microscopic electronic and vibrational parameters, in this work, we use density functional theory (DFT) to study the molecular structures, electron affinities, and IR-active vibrational frequencies as well as thermodynamic properties for c-C4F8 and a series of mono-, di-substituted c-C4F8 compounds. It is shown that DFT calculation of perfluoro-compounds is sensitive to the chosen functional. Although all chloro-substituted c-C4F8 molecules are found to have much larger electron affinities, only part of them have less IR intensity in the atmospheric IR “window” than c-C4F8. Such a study provides useful guideline for the pre-screening search for new insulation gases via electronic structure calculations.